Intonation and Its Effect on Expressing the Meaning in Grammatical Structures in the Sermons of Nahj Al-Balagha - Khalif, Zahraa Suleiman; Abbas, Suhad Jassim (Journal of Ecohumanism, 2024)
Speech does not proceed at a single vocal pace, but rather its tone rises, falls, and levels out, and the pitch of the voice can play an important role in directing the meaning within grammatical styles.UnderstandtheMany syntactic structures such as interrogation, exclamation, vocative, and imperative., and warning through tone, andThe function of intonation does not stop at understanding some grammatical structures, but rather extends to replacing the tone with the tool, as we find in some structures such as the conditional, exclamatory, and interrogative.Our research studies the effect of intonation within grammatical structures, and also attempts to prove the strong connection between vocal intonation and the effect that follows it in directing meaning, through selected examples from the sermons of Nahj al-Balagha.